The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1806-9282.64.03.253
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ceftazidime-avibactam in the treatment of complicated intra-abdominal infections (CIAIs) and complicated urinary tract infections (CUTIs): A meta-analysis of randomized controlled trials

Abstract: Efficacy and safEty of cEftazidimE-avibactam in thE trEatmEnt of complicatEd intra-abdominal infEctions (ciais)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In the subgroup of patients with UTI, higher microbiological cure rates were demonstrated with CAZ-AVI at TOC. Similar results of higher microbiological cure with CAZ-AVI were also reported in a meta-analysis by Zhang et al, compiling trials of patients with cUTI and cIAI (81). Though no significant difference was demonstrated for the outcome of any adverse events (AEs), the rate of serious AEs (SAEs) was significantly higher with CAZ-AVI versus comparator, mostly carbapenem.…”
Section: Clinical Datasupporting
confidence: 80%
“…In the subgroup of patients with UTI, higher microbiological cure rates were demonstrated with CAZ-AVI at TOC. Similar results of higher microbiological cure with CAZ-AVI were also reported in a meta-analysis by Zhang et al, compiling trials of patients with cUTI and cIAI (81). Though no significant difference was demonstrated for the outcome of any adverse events (AEs), the rate of serious AEs (SAEs) was significantly higher with CAZ-AVI versus comparator, mostly carbapenem.…”
Section: Clinical Datasupporting
confidence: 80%
“…In addition, results of individual RCTs have been pooled into secondary research studies, including meta-analyses and post-hoc analyses, for supporting the hypothesis that CAZ-AVI is superior to SoC for infection due to bacteria with special AMR profile. 6,[24][25][26] As it is typical when multiple meta-analyses are produced, the conclusions and the emphasis placed on the results vary among them and their results may become conflicting and even misleading. [27][28] In particular, some studies confirmed no significant difference between treatment arms, [29][30] some studies claimed better efficacy of the experimental intervention for MDR bacteria [25][26] while other studies suggested that the experimental intervention was more toxic than the comparator.…”
Section: Ceftazidime/avibactam: An Overview Of Current Knowledge Frommentioning
confidence: 99%
“…6,[24][25][26] As it is typical when multiple meta-analyses are produced, the conclusions and the emphasis placed on the results vary among them and their results may become conflicting and even misleading. [27][28] In particular, some studies confirmed no significant difference between treatment arms, [29][30] some studies claimed better efficacy of the experimental intervention for MDR bacteria [25][26] while other studies suggested that the experimental intervention was more toxic than the comparator. 24 Non-inferiority randomized controlled trials for antibiotics: ethical and clinical practice implications NI-RCTs are typically presented as a pragmatic design that can compare a new intervention against an established SoC.…”
Section: Ceftazidime/avibactam: An Overview Of Current Knowledge Frommentioning
confidence: 99%
See 1 more Smart Citation